2010
DOI: 10.1007/s00464-009-0875-7
|View full text |Cite
|
Sign up to set email alerts
|

The safety and utility of prophylactic pancreatic duct stents in the prevention of post-ERCP pancreatitis: an analysis of practice in a single UK tertiary referral center

Abstract: A strategy of prophylactic PD stents in this study has eliminated severe post-ERCP pancreatitis in high-risk patients. However, the high pancreatitis rate in stented patients may represent the cost to achieve this, while stent type and size employed are likely contributing factors. To maximize the benefits of PD stenting, there is a need to identify and treat all those considered at high risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In addition, there was a reduction in mild and moderate pancreatitis but not severe pancreatitis. This is in contrast to other studies in which pancreatic duct stent placement virtually eliminated severe PEP [7,8]. Although a variety of adverse events related to pancreatic duct stents are listed in the article by Mazaki et al [6], many are probably not direct effects of pancreatic duct stent placement but due instead to the procedure itself.…”
mentioning
confidence: 79%
“…In addition, there was a reduction in mild and moderate pancreatitis but not severe pancreatitis. This is in contrast to other studies in which pancreatic duct stent placement virtually eliminated severe PEP [7,8]. Although a variety of adverse events related to pancreatic duct stents are listed in the article by Mazaki et al [6], many are probably not direct effects of pancreatic duct stent placement but due instead to the procedure itself.…”
mentioning
confidence: 79%
“…Documents regarding the benefits of PD stent GMJ.2015;4(2):67-71 www.gmj.ir in reducing post-ERCP pancreatitis are increasing. In this context, some case control studies revealed that PD stent insertion considerably reduced the incidence of post-ER-CP pancreatitis certainly among high-risk patients [1,4,8,10,13]. On the other hand, other studies revealed opposite results [2].…”
Section: Discussionmentioning
confidence: 99%
“…In two casecontrolled trials (42,43) and one retrospective analysis (44), pancreatic stent placement decreased the incidence of PEP. In one survey, the PEP rate did not decrease with stent placement, but moderate and severe pancreatitis were seen less often in patients in whom a stent was inserted (45). In a meta-analysis (46) of five controlled studies, PEP incidence was found to be one-third lower in patients in whom a stent was inserted compared to patients with no stent insertion (5.8% vs. 15.5%; p=0.001).…”
Section: Mechanical Reduction Of Pressure In the Pancreatic Duct -Panmentioning
confidence: 99%